This preview shows pages 1–4. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: Granillo, Yvette Homework 13 Due: Nov 24 2005, 3:00 am Inst: Edward Odell 1 This printout should have 23 questions. Multiplechoice questions may continue on the next column or page find all choices before answering. The due time is Central time. 001 (part 1 of 1) 10 points Determine which, if any, of the following f ( x ) = 16 x + 12 , g ( x ) = 4 2 x +3 , h ( x ) = 64 (16 x ) , define the same function. 1. only g, f 2. f, g, and h 3. none of f, g, or h 4. only g, h correct 5. only f, h Explanation: By the Laws of Exponents, f ( x ) = 16 x + 12 = (4 2 ) x + 12 = 4 2 x + 12 , while g ( x ) = 4 2 x +3 and h ( x ) = 64 (16 x ) = (4 3 )(4 2 ) x = (4 3 )(4 2 x ) = 4 2 x +3 . Thus g and h define the same function. On the other hand, f (0) = 13 , g (0) = 64 = h (0) , so neither g nor h can define the same function as f . Consequently only g, h define the same function. keywords: Stewart5e, 002 (part 1 of 1) 10 points If x 1 , x 2 are the solutions of the equation 7 3 x 2 = 1 49 4 x +2 , compute the value of  x 1 + x 2  . 1.  x 1 + x 2  = 8 3 correct 2.  x 1 + x 2  = 4 3 3.  x 1 + x 2  = 2 4 3 4.  x 1 + x 2  = 2 4 3 5.  x 1 + x 2  = 8 3 Explanation: Since 1 49 4 x +2 = 7 8 x 4 , the equation can be written as 7 3 x 2 = 7 8 x 4 , which in turn can be rewritten as 3 x 2 = 8 x 4 by taking logs to the base 7 of both sides. By the quadratic formula, therefore, x 1 , x 2 = 4 4 3 . Thus  x 1 + x 2  = 8 3 . keywords: Stewart5e, 003 (part 1 of 1) 10 points Granillo, Yvette Homework 13 Due: Nov 24 2005, 3:00 am Inst: Edward Odell 2 Which function has 2 4 2 4 2 4 2 4 as its graph? 1. f ( x ) = 2 2 x 1 2. f ( x ) = 3 x 3 3. f ( x ) = 2 x 1 3 4. f ( x ) = 2 3 x 5. f ( x ) = 3 x 2 correct 6. f ( x ) = 2 x 1 2 Explanation: The given graph has the property that lim x f ( x ) = 2 . But lim x 2 x = 0 = lim x 3 x , while lim x  2 x = 0 = lim x  3 x , so f ( x ) must be one of 3 x 2 , 2 x 1 2 . On the other hand, the yintercept of the given graph is at y = 1. Consequently, the graph is that of f ( x ) = 3 x 2 . keywords: Stewart5e, 004 (part 1 of 1) 10 points Find the value of lim x e 3 x 4 e 3 x 2 e 3 x + e 3 x . 1. limit = 2 2. limit = 2 3. limit = 1 4. limit = 1 2 correct 5. limit = 1 6. limit = 1 2 Explanation: From the graph of e x it follows that lim x e kx = 0 , lim x  e kx = 0 for each k > 0. Now e 3 x 4 e 3 x 2 e 3 x + e 3 x = 1 4 e 6 x 2 + e 6 x . But by properties of limits lim x 1 4 e 6 x 2 + e 6 x = 1 2 Consequently, limit = 1 2 . keywords: Stewart5e, Granillo, Yvette Homework 13 Due: Nov 24 2005, 3:00 am Inst: Edward Odell 3 005 (part 1 of 1) 10 points Find the value of f (0) when f ( x ) = 1 3 e 2 x + 1 2 e 2 x ....
View Full
Document
 Spring '08
 schultz

Click to edit the document details